Tahapan Penyelesaian Sengketa Tanah Ulayat di Nagari Tungka Kabupaten 50 Kota Melalui Lembaga KAN Berdasarkan Adat Salingka Nagari - Linda Rachmainy; Hazar Kusmayanti; Hadri Yanti Azizah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Ulayat land disputes are land disputes over ulayat rights that occur in the Minangkabau customary law community. The provisions of Article 12 paragraph (1) of the West Sumatra Regional Regulation Number 6 of 2008 concerning Communal Land and Its Utilization states that Communal Land Disputes in Nagari are resolved by the Nagari Adat Density (KAN) according to the provisions as long as the applicable custom, 'bajanjang naiak Batanggo turun' and endeavored by way of peace through deliberation and consensus in the form of a peace decision. KAN plays a role in resolving ulayat land disputes that occur in every nagari in West Sumatra. Still, based on the adat salingka of the nagari, every ulayat land dispute that occurs is adjusted to the respective customary law. Based on this, each nagari has differences in resolving ulayat land disputes, especially those that arise in Nagari Tungka, District 50, City of West Sumatra. The research was carried out using normative juridical methods with qualitative juridical analysis methods, which combined primary data obtained at the Tungka KAN Institute and field studies through interviews with ninik mamak Nagari Tungka. Stages of resolving ulayat land disputes in Nagari Tungka based on the salingka nagari custom peace, then by Article 12 paragraph (1) West Sumatra Regional Regulation No. 6 of 2008 concerning ulayat land, further dispute resolution is carried out by the KAN institution.